Hydrographic behavior of the drainage basins that intersect Las Grutas town, Argentina - Genchi, Sibila Andrea (2011)
The town of Las Grutas, in a semiarid region on the north west coast of San Matías Gulf (Argentina), is intersected by two drainage basins that are activated immediately after intense rainfall events. These events generate flows capable of producing local flooding, such as the flood of April 2004. The purpose of this study is to establish the hydrologic behavior of these geoforms and the manner in which the land use interacts with them. The lack of hydrometric records necessitates the explanation and prediction of hydrologic responses through empirical approaches such as fluvial morphometry and the USDA Soil Conservation Service curve number (1972), supported by Geographical Information System technology. The study area has characteristics that favor the concentration of runoff into streams during extreme events. First-order segments play an important role in the hydrologic response, showing great potential to receive surface runoff. The effect of urbanization produces an additional runoff of 17.3% and 2.1% in the respective basins. A potential increase in the number of these extreme events in the future due to climate change may lead to more disturbances in the urbanized area. The results of the present study will contribute to the implementation of measures to mitigate the consequences of floods.